La compliance en droit bancaire et financier, une fonction juridique et managériale - Amoussou, Henry (Université de Reims Champagne-Ardenne, 2024)
La compliance s’est traduite par une floraison des obligations, des techniques et des procédures, portées par des règles de ''droit dur'' et de ''droit souple''. Leurs mises en œuvre ont été confiées à de nouveaux acteurs. Dans le domaine bancaire et financier, loin de dénaturer la conformité et la régulation, la compliance les renforce en étendant les obligations de cartographie des risques et de vigilance aux risques de corruption et environnementaux. Cependant, le blanchiment de capitaux et le financement du terrorisme restent les risques dominants. Ils sont au cœur de la compliance, notamment au regard de l'activité de sanctions de l’Autorité de contrôle prudentiel et de résolution (ACPR). La prévention de ce risque impose la mise en application des dispositifs normatifs que sont les principes de cartographie des risques et de vigilance. Au-delà de la conformité aux principes normatifs (juridique), la compliance mobilise toutes les fonctions de l’entreprise au niveau opérationnel (management). Ces fonctions opérationnelles sont relatives aux procédures d’alerte, de signalements, de contrôles, de sanctions et constituent des dispositifs procéduraux. Pouvant être qualifiée en ce sens, de « fonction juridique et managériale », la compliance pousse à envisager autrement les régimes de responsabilités en milieu bancaire et financier, fondés sur des défaillances ''obligationnelles'', tant juridiques que managériales. Cela renvoie à l’épineuse obligation de connaissances en management requises pour les juristes et les autorités d’une part, et d'autre part, au caractère inextricable des fonctions juridiques et managériales (d’où les formations en droit des affaires et management).
Keywords: Compliance; Conformité; Droit bancaire; Droit financier

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

La titrisation - Chambon, Benoît (Université Paris-Est, 2024)
Près de dix ans après la crise des subprimes les opérations de titrisation connaissent un nouvel essor. Ce dernier fait suite notamment à des travaux de la Commission européenne qui, dès 2015, a fait part de son intention de réviser le corpus applicable à ces transactions dans la cadre de son plan d'action pour la construction de l'Union des Marchés de Capitaux. C'est ainsi qu'en 2017 un règlement portant sur les opérations simples transparentes et standardisées a été publié au journal officiel de l'Union européenne. Ce texte a vocation à être complété par un autre règlement relatif à l'opposabilité des cessions de créances. Au niveau international les règles de rétention de fonds propres applicables visant les expositions de titrisations ont été amendées afin de mieux prendre en compte les risques y attachés. En France le régime applicable à la gestion d'actif et au financement par la dette a été remanié. On peut se demander comment ces évolutions normatives ont influencé la manière dont les risques systémiques et idiosyncratiques sont créés, transférés et couverts dans le cadre des opérations de titrisation. Almost ten years after the subprime crisis, securitization transactions are experiencing a new boom. The latter follows notably work of the European Commission which, as early as 2015, announced its intention to revise the legal framework applicable to these transactions as part of its action plan for the Capital Market Union. This led in 2017 to the publication in the Official Journal of the European Union of a regulation on simple, transparent and standardized transactions. This text is intended to be supplemented by another regulation on the enforceability of assignments of receivables. At the international level, the capital retention rules applicable to securitization exposures have been amended to take better account of the risks associated to said exposures. In France, the legal framework applicable to asset management and debt financing has been revised. One can wonder whether the normative developments have influenced the way systemic and idiosyncratic risks are created, transferred and hedged in securitization transactions.
Keywords: Idiosyncratic risks; Risque idiosyncratique; Risque systémique; Securitization; Systemic risks; Titrisation

Les jetons participatifs : contribution au droit de la finance participative - Aliyev, Novruz (Université de Rennes, 2024)
Au-delà de l’aspect numérique, Satoshi, fondateur anonyme du bitcoin, évoque l’organisation de « Pair à Pair » (P2P). Elle correspond à l’algorithmique répartie sur laquelle le registre décentralisé de ces nouveaux actifs se fonde. Mais le Règlement MiCA exclut la finance décentralisée et ne donne aucune définition satisfaisante des crypto-actifs. On étend cette observation aux actifs numériques, insuffisamment cernés en droit français. L’analyse de l’organisation P2P s’impose. On a identifié chez certains jetons une organisation participative, distincte des groupements et des contrats-coopération. Elle se caractérise par un degré et une forme d’indépendance nouvelle ainsi que par une socialité orientée vers un objet de nature impersonnelle, ouverte vers l’extérieur et sans structure (ni groupements ni contrats). Elle façonne ainsi la structure d’émission et la forme représentative et négociable de ces jetons. Ils sont des écrits représentant un bien ou un service et non un droit à l’encontre d’une personne émettrice. Ils sont émis dans une organisation participative : sans partage de pertes, de bénéfices, de chiffres d’affaires ou d’autres fruits. Leur qualification civiliste est le produit et non le fruit, contrairement aux titres financiers. L’organisation participative, elle, s’analyse comme un système, une nouvelle catégorie juridique que l’ordre juridique peut accueillir. L’ouverture du système vers l’extérieur nécessite la négociabilité des jetons. Elle concourt à la financiarisation de l’économie réelle. Comme la structure d’émission de ces jetons participatifs, leur infrastructure polycentrique de négociation appelle une régulation par l’organisation. Ces jetons sont aussi hybrides parce que participatifs et monétaires, et en tant que tels peuvent être considérés comme des unités de financement ; nouvelle définition de la monnaie que l’on propose, pour ne pas la réduire à sa seule fonction de paiement. Les jetons participatifs perturbent la summa divisio entre la monnaie et les instruments financiers ainsi que le concept même de droit subjectif.
Keywords: Crypto; Crypto-Actifs; Cryptomonnaie; Decentralised finance; Distributed ledger technology.; Finance décentralisée; Financement participatif; Jeton; Jetons-monnaie; Monnaie; Registre réparti; System; Système; Token

Les financements sur une blockchain : nouveaux défis du droit financier à l'aune de la finance décentralisée - Bonnet, Joris (Université de Strasbourg, 2024)
Alors que la finance traditionnelle peine à se renouveler, les nouveaux applicatifs de finance décentralisée proposent des services financiers basés sur des protocoles innovants, codés et entièrement gérés par les utilisateurs. Les classifications historiques de la finance sont largement inefficaces et des catégories telles que celle des instruments financiers ne permettent pas de construire un encadrement pertinent. Celles-ci doivent être dépassées pour pouvoir encadrer de façon plus inclusive tous les actifs décentralisés. La communication financière est rendue désuète et nécessite une refonte pour prendre en compte les nouvelles motivations des investisseurs et les impératifs environnementaux. Traditional finance is struggling to renew, new decentralized finance applications offer financial services based on coded protocols entirely managed by users. Historical classifications of finance are largely ineffective and categories such as financial instruments do not allow to construct a relevant framework. These must be overcome to be able to regulate all decentralized assets in a more inclusive manner. Financial communication has become obsolete and requires an overhaul to consider the new motivations of investors and environmental imperatives.
Keywords: Actif décentralisé; Asset; Blockchain; Chaine de blocs; Contract; Contrat; Crypto money; Crypto monnaie; Cryptoactif; Cryptomonnaie; DAO; DEEP; DLT; DeFi; Decentralized asset; Decentralized finance; Droit des affaires; Droit financier; Finance décentralisée; Finances; Financial law; Fundraising; ICO; Jeton; Levée de fonds; STO; Security; Token

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud